EARLY DETECTION STUDY OF ANCIENT SITES UNDER THE SURFACE BASED ON THE COMBINATION OF GEOLISTRIC METHODS WITH GEOMAGNETIC METHODS IN TAPANULI TENGAH - Asdiati Berutu; Jamaludin Hasibuan; Halimahtun Sakdiah; Rahmatsyah Rahmatsyah (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
Indonesian nation is renown as a nation that has cultural heritage of high value, one of them is the relics of archaeological sites of Barus Kingdom in Lobu Tua Tapanuli Tengah regency. Have to be investigated using study early detection of the presence of archaeological sites by based combintion geoelectric method with geomagnetic which aims to determine the presence of the sites in Lobu Tua based combination geoelectric method with geomagnetic. Date processing is done by geoelectric research area is dominated by alluvium rock with the resistivity 55,3 – 705 at depth 6 m - 30 m and tuff with the resistivity 2600 – 4601 at depth 1,25 m - 6 m and andesite rocks with the resistivity 500 – 2300. Qualitatively, the result shows there are magnetic anomalies part with high value is -90 nT, susceptibility value ranged between 0,714 – 0,994 interpreted with sand and susceptibility value ranged between 1,008 - 1,261 interpreted with alluvium rocks. So the research area of archaeological sites in the city of Barus dominated by alluvium rock. Where from Of both methods Can be interpreted rock archaeological sites in the city of Barus with alluvium rocks.